Computational study of electronic, optical and thermoelectric properties of X3PbO (X = Ca, Sr, Ba) anti-perovskites. (29th September 2017) - Hassan, M; Arshad, I; Mahmood, Q
Abstract: We report the structural, electronic, optical and thermoelectric (TE) properties of X3 PbO (X = Ca, Sr, Ba) anti-perovskites as a function of X cations belonging to the group IIA. The computations are done by using the most recently introduced modified Becke–Johnson potential. It has been observed that the cubic lattice constant increases as the cations change from Ca to Ba, consequently, the bulk modulus reduces. The bottom of conduction band shows strong hybridization between Pb-6p, O-2p and X-s states, in contrast, valence band maxima are mainly manufactured by Pb-6p states. The anti-perovskites exhibit narrow direct band gap that show an inverse relation to the static real dielectric constants that verifies Penn's model. In addition, the X cations induced tuning of the absorption edge in the visible and the ultraviolet energy suggest optical device applications. The computed TE parameters have been found sensitive to the X cations and have been demonstrated to be best suited for the TE devices operating at high temperatures.